The Relationship between Listening Anxiety and Listening Comprehension of English Department Students in Basic Listening Classes at Universitas Negeri Padang - Suci Rahma Annisa; Aryuliva Adnan; Leni Marlina (Journal of English Language Teaching, 2020)
Listening anxiety which makes someone feel tensions, fear, uncomfortable, and worry was suspected to affect students' comprehension in listening class. Therefore, this research aims to find the relationship between listening anxiety and listening comprehension of English department students who had taken the Basic Listening class at Universitas Negeri Padang. The type of research used in this research was quantitative research. The population of this research was the second-year students in Basic Listening Class of English Department. The sample was 60 students who were chosen randomly from the total population using Simple Random Sampling. The data were collected through a questionnaire and an English listening comprehension test using Basic Listening final examination test. The results showed that Foreign Language Listening Anxiety (FLLA) and Listening Comprehension (LC) have a negative correlation (r= -.245) which indicates that high anxiety blocks the processing of listening comprehension, and when the higher anxiety the students have, the lower listening comprehension they get. Further research related to listening comprehension and listening anxiety is suggested to do.